RtPA for Submacular Hemorrhage: Mechanisms, Administration Routes, and Therapeutic Strategies - Zabrzeński, Bartosz; Schendzielorz, Jessika; Pośpiech, Szczepan; Prosowski, Jakub; Serwicki, Piotr; Piotrowski, Michał; Chodkowska, Ewa; Bielas, Kinga; Mucha, Aleksandra; Szeps, Aleksander (Quality in Sport, 2025)
Aims: This review aims to evaluate the clinical utility of recombinant tissue plasminogen activator (rtPA) in submacular hemorrhage (SMH) by characterizing its mechanisms of action, comparing intravitreal versus subretinal delivery routes, assessing adjunctive strategies—including anti‐VEGF and pneumatic or hybrid techniques—and summarizing safety and complication profiles. Methods: We performed a systematic PubMed search (up to April 2025) using “rtPA” OR “recombinant tissue plasminogen activator” AND “submacular hemorrhage” OR “subretinal hemorrhage.” Publications from January 2019 onward were prioritized, except foundational mechanistic studies without a date limit. After screening titles and abstracts (n = 69) and reviewing full texts (n = 61), 29 studies met inclusion criteria (clinical adult SMH, rtPA dosing/route, and specified outcomes). Study types included one randomized controlled trial, one meta‐analysis, eight retrospective cohorts (≥ 25 eyes), twelve case series (5–24 eyes), and seven case reports. Results: Mechanistic data confirm fibrin‐selective plasminogen activation by rtPA. Intravitreal rtPA plus gas achieved clot displacement in 75–90% of eyes (mean LogMAR VA improvement from 1.2 to 0.8 at six months), while subretinal injection yielded ≥ 90% clearance and comparable or superior functional gains. Adjunctive anti‐VEGF and hybrid subretinal air + rtPA + anti‐VEGF approaches further improved outcomes. Overall adverse event rates ranged from 20% to 25%, including vitreous hemorrhage, retinal detachment, macular hole formation, and RPE tears. Conclusions: rtPA—administered intravitreally or subretinally—combined with pneumatic displacement and anti‐VEGF, provides effective SMH management. Notwithstanding encouraging results, complications and reliance on retrospective data highlight the need for standardized protocols and prospective trials such as TIGER.